Blurred Lines? Provincial Reconstruction Teams and NGO Insecurity in Afghanistan, 2010–2011. Issue 1 (4th March 2015) - Mitchell, David F.
Members of nongovernmental organizations (NGOs) have been critical of the Provincial Reconstruction Team (PRT) initiative in Afghanistan since its inception, claiming that the mixture of military and humanitarian operations has resulted in 'blurred lines' that inhibit insurgents from identifying who is and is not a combatant. Certain organizations have hypothesized that aid workers are more likely to come under attack as a result of this mixture. Although this claim has surfaced in multiple outlets over the years, there was a lack of empirical evidence to support it. This study tests this hypothesis using a panel-corrected standard error regression model of all 34 Afghan provinces in 2010 and 2011. Preliminary results show that NGOs were likely to encounter a greater number of security incidents in provinces with PRTs; however, further analysis reveals this was only the case in provinces with teams not led by the US. This calls into question the validity of a general 'blurred lines' explanation for decreased aid worker security.